Fungal derived dye as potential photosensitizer for antimicrobial photodynamic therapy - de Lima, Isabelle Almeida [UNESP] (2025)
Photodynamic therapy (PDT) combines light with a photosensitizing agent to target and destroy abnormal cells or pathogens, offering a non-invasive and precise approach. Applying microbial dyes in PDT presents a great opportunity because these compounds may absorb specific wavelengths of light, generating reactive oxygen species (ROS) that induce oxidative stress, leading to cell or microbial death. This study evaluated the extract of Talaromyces amestolkiae containing azaphilone red dyes obtained from cultivation process as photosensitizer (PS) in antimicrobial photodynamic therapy (aPDT). Initially the crude extract was obtained in incubator shaker varying the culture media composition. Following, the crude extract containing the red dyes exhibited non-toxicity in dark conditions across all concentrations tested. PDT experiments with different amounts of the crude extract at a light dose of 80 J.cm-2 and upon irradiation at 460 nm was studied. A complete reduction of Escherichia coli and approximately 2 log10 reductions of Staphylococcus aureus, Cutibacterium acnes and Enterococcus faecalis was achieved using 25 % (v.v-1) of the crude extract while 50 % (v.v-1) of the crude extract led to a complete reduction of both E. coli and S. aureus, and around 5 log10 reductions of C. acnes and E. faecalis. Importantly, minimal photodegradation of the PS occurred during irradiation across all concentrations studied. These findings highlight the potential of T. amestolkiae-derived red dyes extract for use in aPDT, demonstrating non-toxicity in the absence of light, good aqueous solubility, high photostability, and strong microbial reduction capabilities under specific light conditions.